2009
DOI: 10.1242/dev.037168
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct types of mouse melanocyte: differential signaling requirement for the maintenance of non-cutaneous and dermal versus epidermal melanocytes

Abstract: Unlike the thoroughly investigated melanocyte population in the hair follicle of the epidermis, the growth and differentiation requirements of the melanocytes in the eye, harderian gland and inner ear -the so-called non-cutaneous melanocytes -remain unclear. In this study, we investigated the in vitro and in vivo effects of the factors that regulate melanocyte development on the stem cells or the precursors of these non-cutaneous melanocytes. In general, a reduction in KIT receptor tyrosine kinase signaling le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(105 citation statements)
references
References 63 publications
5
98
1
Order By: Relevance
“…We conclude that both surrounding environment and genetic context influence the proliferation rate of melanoblasts during development. Those findings are consistent with those of Kunisada, suggesting that specific factors influence melanocyte survival/growth/differentiation as a function of their location in the skin (Aoki et al, 2009). This model provided no evidence, either mathematical or experimental, for a second major wave of melanoblast production, at the body location and stages of development analyzed (Adameyko et al, 2009;Jordan and Jackson, 2000).…”
Section: Establishment Of the Melanocyte Lineagesupporting
confidence: 90%
“…We conclude that both surrounding environment and genetic context influence the proliferation rate of melanoblasts during development. Those findings are consistent with those of Kunisada, suggesting that specific factors influence melanocyte survival/growth/differentiation as a function of their location in the skin (Aoki et al, 2009). This model provided no evidence, either mathematical or experimental, for a second major wave of melanoblast production, at the body location and stages of development analyzed (Adameyko et al, 2009;Jordan and Jackson, 2000).…”
Section: Establishment Of the Melanocyte Lineagesupporting
confidence: 90%
“…In the case of Aves, EDNRB2 is thought to be important for melanoblast migration toward the usual "dorsolateral" pathway (Pla et al 2005;Harris et al 2008). On the other hand, Aoki et al (2009) demonstrated that noncutaneous and dermal melanocytes are more sensitive to EDN3 for growth and differentiation compared with epidermal melanocytes. In Silky fowl, excess EDN3 may affect only the proliferation of the dermal melanocyte cell lineage during the early differentiating stage.…”
Section: Discussionmentioning
confidence: 99%
“…With minor modifications, the method for the induction of neural lineage was the same as previously described (41,42). For differentiation, 1,000 trypsinized ES cells were inoculated on a monolayer of PA6 cells previously seeded on 6-well plates (BD Falcon).…”
Section: Methodsmentioning
confidence: 99%
“…The cultures were also exposed to 20 pM cholera toxin (Wako) from days 0 to 3, and the medium was changed every 3 days. In some experiments, 100 ng/ml recombinant Kitl (BioLegend) and 10 μg/ml rat monoclonal antibody ACK2, which can block Kit function (42,43), were added into the culture on the indicated days. In the indicated experiment, Rosa26::rtTA; Col1a1::tetO-Cre; Kit 2lox/+ ES cells were treated with 2 μg/ml doxycycline.…”
Section: Methodsmentioning
confidence: 99%